The Undifferentiated Chest Pain Patient - An Introduction to the ED Approach to the Patient - Corey Heitz; John H. Burton; Timothy J. Fortuna; Damon R. Kuehl; John C. Perkins; Melanie K. Prusakowski (Association of American Medical Colleges, 2013)
Abstract Introduction In emergency medicine, we evaluate and treat patients with chief complaints and need to have a thorough understanding of elements of the domains of training during our care. This educational module was developed to demonstrate these multidimensional aspects of emergency department (ED) care. Given this, the module ties in the various aspects of clinical medicine, emphasizing to the students that clinical care involves all aspects of their discipline including basic science, clinical science, research, and interprofessionalism. Our session was specifically designed to give third-year medical students the opportunity to make clinical decisions and apply their prior education and research skills to patient care. For many, this is the first time they were responsible for direct care of a patient. We chose the chief complaint of chest pain as it is a common one with a wide variety of potential problems and diagnoses, and brings to bear elements of all aspects of medicine. Methods This module represents a multidisciplinary approach to the evaluation of a patient with chest pain in an ED setting, and is designed for medical students of various levels. Students are initially in a large-group setting (group size may vary), where they receive a didactic lecture regarding the emergency medicine thought process and an introduction to the educational activity. They are then divided into small groups to perform a case-based literature search on specific topics, and then return to the large group where four facilitated simulations are performed (ST myocardial infarction, acute coronary syndrome, aortic dissection, and pneumothorax). A discussion regarding the integration of clinical sciences, basic sciences, research, and interprofessionalism occurs at the end. Results At the end of the session, students filled out an evaluation using a 5-point Likert scale (5 = strongly agree). These individual scores were then averaged by item. To the item "This experience has helped me develop the skills necessary to care for patients," students gave an average score of 4.27. To the item "I was challenged in my thinking and decision-making skills," students gave a score of 4.17. To the item "This experience enhanced my understanding of the integration of basic and clinical sciences," students gave a score of 4.21. To the item "This experience enhanced my understanding of the application of interprofessionalism," students gave a score of 3.76. Discussion At the Virginia Tech Carilion School of Medicine, medical student education is guided by the various domains of medicine - basic science, clinical science, research, and interprofessionalism. During their third year, the medical students are brought back from clerkship rotations for large-group sessions run by each department, highlighting how that individual department's care and approach to the patient are guided by and incorporate all of the different domains. This educational course was developed to demonstrate that multidimensional aspect of ED care.